Tailoring microstructure and photovoltaic effect in multiferroic Nd-substituted BiFeO3 ceramics by processing atmosphere modification. Issue 4 (April 2018) - Tu, Chi-Shun; Chen, Pin-Yi; Chen, Cheng-Sao; Lin, Chun-Yen; Schmidt, V.H.
Abstract: This study highlights significant effects of processing atmosphere ratio (O2 /N2 ) on microstructure, impurity phases, atomic hybridization, band gap, and photovoltaic properties in (Bi0.93 Nd0.07 )FeO3 (BFO7Nd) ceramics. A Rietveld-refinement analysis indicates increased oxygen and bismuth vacancies in the specimens processed in the O2 -rich atmosphere (hereafter called O2 -rich-atmosphere specimens). In the matrix containing mainly Fe 3+ ions, Fe 4+ cations were identified with O2 concentration decreasing in the atmosphere by Fe K/L-edges synchrotron X-ray absorption. Oxygen K-edge absorption reveals reduced hybridizations of the O 2 p –Fe 3 d and the O 2 p –Bi 6 sp orbitals in the O2 -rich-atmosphere specimens. Photovoltaic effects in the ITO/BFO7Nd/Au heterostructures under near-ultraviolet irradiation (λ = 405 nm) exhibit strong dependences on O2 /N2 ratio. A p - n -junction model was used to describe open-circuit voltage and short-circuit current density as functions of irradiation intensity. The calculated carrier densities (in BFO7Nd ceramics) and p - n -junction widths (in the dark) are ∼10 23  m −3 and a few hundred nanometers, respectively.